(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The essence of project activity is considered as one of the ways to stimulate personal growth and social formation. The principle and conditions of the organization of project activities when working with students are analyzed.